Grennan & Sperandio : Nurse's Tale as told to Grennan & Sperandio. (Seattle : Fantagraphics Books Seattle, 2000)
Nurse's Tale is a collection of ordinary and extraordinary stories of life in the Hastings and Rother N H S Trust, told to Grennan & Sperandio by friends, patients and staff. Each story makes deep Comic Cuts into the Heart of the trust, revealing some of its complex Inner Workings, both social and professional. Nurse's tale is a unique Sample of the people who make the trust what it is - a Major Operation in the continuing Welfare of the region.
Engels
boek
Keywords: Grennan & Sperandio; Grennan, Simon; Sperandio, Christopher